Ultrathin 2D Cu-porphyrin MOF nanosheets as a heterogeneous catalyst for styrene oxidation. (5th June 2019) - Xiao, Yawen; Guo, Wenxiao; Chen, Huanhuan; Li, Hongfeng; Xu, Xiujie; Wu, Peng; Shen, Yu; Zheng, Bing; Huo, Fengwei; Wei, Wei David
Abstract : Cu-TCPP nanosheets exhibit a high density of active sites and low diffusion barriers for styrene epoxidation. Abstract : 2D MOF nanostructures have shown promising properties in heterogeneous catalysis. Herein, we synthesized ultrathin 2D Cu-porphyrin MOF nanosheets and demonstrated their excellent catalytic performance in styrene oxidation (94% conversion efficiency), which was attributed to the material's high density of exposed active sites and low diffusion barriers.